Way Forward for Teacher Professional Development in Kenya: Utilization of Performance Appraisal Reports - Damaris Kariuki; Hellen Guantai (European Scientific Journal, ESJ, 2020)
Performance appraisal in the education sector has attracted scholarly interests globally. This is because critical feedback obtained from performance appraisal reports could be used to inform professional development needs of teachers. The purpose of this study was to establish the extent to which performance appraisal reports informed professional development of teachers in public secondary schools in Kenya. The study objectives were to establish the extent to which performance appraisal reports are used to inform identified teacher professional development gaps and find out the challenges encountered in the utilization of performance appraisal reports in informing teacher professional development. Mixed methods research design was used. The target population comprised 70 Principals, 210 Heads of Departments and 210 teachers giving a total of 490 respondents. Stratified and simple random sampling techniques were used to select a sample size of 98 respondents. Questionnaires and interview schedule were used to collect data. Descriptive statistics were used to analyze quantitative data while qualitative data were analyzed thematically. The study established that performance appraisal reports were not being used to inform teacher professional development activities. This was occasioned by inadequate head teacher and heads of department capacity on their role in teacher appraisal and professional development and limited resources to put in professional development interventions at the school level. The study recommended adoption of enhanced mechanisms to obtain appraisal reports, collate them and identify areas of professional development intervention.